(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This System consists of asedimentation tank, two units of anaerobic digester and two units of up-flow filters. Thefinal effluent released from the system is found to be within permissible limits, which further could be used for recreational purposes like gardening, plantation, flushing inbathrooms, W.C, etc. In this study the parameters of waste water such as pH, Turbidity, TS, TSS, TDS, BOD5, COD were observed upto the 1.5 hr of detention period and at theflow rate of 12Lhr. Initially the effluent concentration pH, Turbidity, TS, TSS, TDS,BOD5, COD were 14, 269 NTU, 6900mgL, 5100mgL, 1800mgL, 46mgL, 110mgLthe corresponding values after passing the waste water through the system for optimizedconditions were 7, 13NTU, 400mgL, 320mgL, 80mgL, 18mgL, 43.2mgLrespectively.